PENERAPAN SENAM ERGONOMIS UNTUK MENURUNKAN KADAR ASAM URAT PADA LANSIA DENGAN INTOLERANSI AKTIVITAS DI PONDOK LANSIA YPA AN-NUR KOTA KEDIRI - Ika Prihananto, Dhian; Risnasari, Norma; Aizah, Siti; Hardianto, Dimas (Judika (Jurnal Nusantara Medika), 2021)
Gout is a disease caused by a buildup of uric acid or crystals in tissues, especially in the joints. One of the non-pharmacological treatments to reduce uric acid levels in patients with gout is doing ergonomic exercise, which is a combination of muscle movement and breathing techniques. This type of research is descriptive using a case study approach. The subjects of this study were two elderly people who suffered from gout with activity intolerance nursing problems by applying ergonomic exercise to reduce uric acid levels. Ergonomic gymnastics research instruments use Standard Operating Procedures (SOP) sheets and instruments to measure uric acid levels using Point Of Care Testing (POCT). The results showed that on the first day Mr. E had high uric acid levels with an amount of 8.2 mg/dl and after receiving ergonomic exercise therapy, Mr. E experienced a decrease in uric acid levels by an amount of 7.7 mg/dl. Mrs.S got the result of 9.6 mg/dl and decreased with the result of 7.2 mg/dl. On the second day, the uric acid level was checked with the result that Tn.E was 7.4 mg/dl and after receiving ergonomic exercise therapy, Mr.E's uric acid level did not change. Mrs. W uric acid level is 7.2 mg/dl and after receiving ergonomic exercise therapy, uric acid level is still 7.2 mg/dl. On the third day, before ergonomic exercise therapy, Mr. E got 6.9 mg/dl but after receiving ergonomic exercise, uric acid levels increased by 7.0 mg/dl. Mrs.S' uric acid level was 5.9 mg/dl and after doing ergonomic exercise therapy, Mrs.S experienced an increase in uric acid with a result of 6.2 mg/dl. The conclusion is that ergonomic exercise has an effect on reducing uric acid levels.